2021
DOI: 10.3390/jcm10173989
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Anxiety, Depression, Attitude, and Coping Strategies of the Egyptian Population during the COVID-19 Pandemic

Abstract: Background: The COVID-19 pandemic has imposed several challenges on different populations all around the world, with stress being identified as one of the major challenges. This study aims to investigate the impact of COVID-19-induced stress on the prevalence and severity of anxiety and/or depression, factors that predict the development of anxiety and/or depression, and coping strategies in the Egyptian population during the COVID 19 outbreak. Subjects and Methods: This is an observational cross-sectional onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 15 publications
2
11
0
Order By: Relevance
“…The same online instruments were used like the prior global study led by the last author (MAR), but the current study adapted German language. In this study, more females participated than males, which was in line with other similar German studies ( 16 , 26 28 ) in the first wave of the pandemic, and also supports an Australian ( 10 ), Egyptian ( 15 ), Bangladeshi ( 14 ), Malaysian ( 13 ), and global study ( 10 ). A possible explanation might be that women were more inclined to share their experiences by participating in the study or women were more impacted due to the pandemic, lockdown or financially that prompted them to participate in the study.…”
Section: Discussionsupporting
confidence: 92%
“…The same online instruments were used like the prior global study led by the last author (MAR), but the current study adapted German language. In this study, more females participated than males, which was in line with other similar German studies ( 16 , 26 28 ) in the first wave of the pandemic, and also supports an Australian ( 10 ), Egyptian ( 15 ), Bangladeshi ( 14 ), Malaysian ( 13 ), and global study ( 10 ). A possible explanation might be that women were more inclined to share their experiences by participating in the study or women were more impacted due to the pandemic, lockdown or financially that prompted them to participate in the study.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, health-related variables (presence of chronic diseases; taking medication regularly; needing to attend consultations in a health centre, hospital, or clinic regularly; having recently performed COVID-19 tests; and self-assessment of health perception) were related to the presence of psychological distress, as had already been described in the studies by Shehata et al [36], Cybulski et al [37], and Ripoll et al [38]. Regarding the evaluation of the perception of the health of our sample, the results show that the group of people who do not experience psychological distress expressed a better evaluation of their health compared to the group that had psychological distress, although both made a good self-assessment of their health.…”
Section: Discussionsupporting
confidence: 66%
“…Our findings indicate thatadvanced age was a protective factor for depression symptoms, but this age variable is not statistically significant for anxiety related models in all present analyses. In the Egyptian population, age was reported to show a significantly negative correlation with depression during the COVID 19 outbreak [25]. A systematic review of Jiaqi Xiong also showed that those from the younger age group (≤40 years) presented with more depressive symptoms [26].…”
Section: Discussionmentioning
confidence: 98%
“…The total score of the PHQ-9 scale after self-reported response ranges from 0 to 27, and more severe depression symptoms are shown by a higher score. Symptom severity was based on the total score and was categorized as follows: absence of depression (0-4), mild depression (5)(6)(7)(8)(9), moderate depression (10)(11)(12)(13)(14), and severe depression (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). In various medical settings, the validated depression scale was reported with good reliability (Cronbach's α = 0.86-0.89).…”
mentioning
confidence: 99%